Roles, Regulation, and Agricultural Application of Plant Phosphate Transporters - Wang, Duoliya; Lv, Sulian; Jiang, Ping; Li, Yinxin (Frontiers in Plant Science, 2017)
Phosphorus (P) is an essential mineral nutrient for plant growth and development. Low availability of inorganic phosphate (orthophosphate; Pi) in soil seriously restricts the crop production, while excessive fertilization has caused environmental pollution. Pi acquisition and homeostasis depend on transport processes controlled Pi transporters, which are grouped into five families so far: PHT1, PHT2, PHT3, PHT4 and PHT5. This review summarizes the current understanding on plant PHT families, including phylogenetic analysis, function, and regulation. The potential application of Pi transporters and the related regulatory factors for developing genetically modified crops with high phosphorus use efficiency (PUE) are also discussed in this review. At last, we provide some potential strategies for developing high PUE crops under salt or drought stress conditions, which can be valuable for improving crop yields challenged by global scarcity of water resources and increasing soil salinization.